Hubungan Beban Kerja dan Komunikasi Interpersonal dengan Burnout Syndrome Perawat Rawat Inap RSUD Brebes: Study Cross-Sectional - Muhammad Dzaky Irawan; Muhammad Riza Setiawan; Susilo Budi Pratama (Universitas Nurul Jadid, 2026)
Burnout syndrome is a condition characterized by emotional, physical, and mental exhaustion that may affect the quality of healthcare services and the performance of nurse inpatient wards. High job demands and ineffective interpersonal communication may increase the risk of burnout syndrome. This study aimed to analyze the relationship between workload and interpersonal communication and burnout syndrome among healthcare workers in the inpatient wards of Brebes Regional General Hospital. This study employed an analytic observational design with a cross-sectional approach. A total of 60 healthcare workers were selected using a consecutive sampling technique. Data were collected using a workload questionnaire, an interpersonal communication questionnaire, and the Maslach Burnout Inventory-Human Services Survey (MBI-HSS). Data were analyzed using Spearman rank correlation tests. The results showed that most respondents were female (60%), aged 24–37 years (56,7%), and had a working period of 4–14 years (60%). The largest proportio majority of respondents had a moderate workload (63.3%), low levels of interpersonal communication (30%), and moderate levels of burnout syndrome (51.7%). Bivariate analysis revealed that both workload and interpersonal communication were significantly associated with burnout syndrome (p<0.001). It can be concluded that workload and interpersonal communication are significantly related to burnout syndrome among healthcare workers in the inpatient wards of Brebes Regional General Hospital. Workload was positively correlated, while interpersonal communication was negatively correlated with burnout syndrome.